Familiarity, Navigation, and Comprehension: Key Dimensions of Health Literacy in Pap Test Use among Korean American Women. Issue 6 (3rd June 2019) - Han, Hae-Ra; Kim, Kyounghae; Cudjoe, Joycelyn; Kim, Miyong T.
Abstract : Health literacy consists of multiple dimensions such as print and oral literacy or numeracy. Different dimensions of health literacy may have more salient impact on certain health behaviors and outcomes. Yet, evidence is limited regarding which dimensions particularly affect cervical cancer screening. The objective of this study was to examine the role of different dimensions of health literacy in cervical cancer screening among Korean American women. We used baseline data obtained from 560 Korean American women in a community-based health literacy-focused intervention study. Backward stepwise logistic regression analysis revealed that familiarity (adjusted odds ratio [AOR] = 1.20, 95% confidence interval [CI] = 1.11–1.31) and navigational health literacy (AOR = 1.10, 95% CI = 1.04–1.16) were associated with lifetime Pap test use and comprehension (AOR = 1.08, 95% CI = 1.02–1.14) with triennial Pap test screening. Prior exposure to healthcare settings and knowing how to navigate the healthcare system were more important than other health literacy dimensions for lifetime Pap test use. Understanding cancer screening-related words was most relevant to triennial Pap test use. In addition to addressing system factors such as insurance and physicians' recommendations, interventions to increase Pap test screening targeted at Korean American women are needed to address certain dimensions of health literacy such as familiarity, navigation, and comprehension.